Hypercalcemia and altered biochemical bone markers in post-bone marrow transplantation osteopetrosis: A case report and literature review - Alisa Kulpiya (2018)
Autosomal recessive osteopetrosis is a rare disorder of bone resorption defect that results in generalized sclerotic bones and bone marrow failure. Allogeneic BMT is the only treatment for cure. One of the complications following a successful BMT is hypercalcemia that is a unique complication in this group of patients. We report a three-yr-old boy with osteopetrosis who developed hypercalcemia following the successful BMT. His maximal calcium level was 13.3 mg/dL. Markedly increased both bone formation and resorption markers were demonstrated along with hypercalcemia. These findings indicated an active donor-derived osteoclastic function and thus bone resorption following the successful donor engraftment in the patient. Treatment with hyperhydration, furosemide and bone resorption inhibitors, calcitonin, and bisphosphonate led to normalization of the serum calcium level. Bone resorption but not bone formation marker was persistently elevated despite having normocalcemia during a 16.5-month follow-up period. © 2011 John Wiley & Sons A/S.